2019
DOI: 10.1007/s40722-019-00132-z
|View full text |Cite
|
Sign up to set email alerts
|

A note on the tuning of tidal turbines in channels

Abstract: Maximising the performance of a tidal turbine array requires the turbine resistance to be 'tuned' for a given channel and turbine arrangement. In many cases, tuning the turbines to produce the maximum power coefficient presents too great a resistance to the incoming flow and results in a lower power output. Recent studies have shown that, as compared to using a fixed tuning, considerably more power can be produced by varying the turbine resistance over the tidal cycle. To our knowledge, however, this higher po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Figures 7 and 8 also show that the amount by which dynamic tuning can enhance P av(max) increases both with B L for a given N, and with N for a given B L . These results are consistent with previous works on turbine tuning, which have shown that the importance of tuning increases with the potential for turbines to exert thrust on the incoming flow and hence affect their own performance [15,18]. The results are also consistent with present understanding of array performance: as B L increases (and B A reduces) for a given N (or as N increases and B A reduces for a given B L ), an array-scale bypass flow is introduced and a reversal boost dynamic is established [8].…”
Section: Dynamic Tuningsupporting
confidence: 92%
See 4 more Smart Citations
“…Figures 7 and 8 also show that the amount by which dynamic tuning can enhance P av(max) increases both with B L for a given N, and with N for a given B L . These results are consistent with previous works on turbine tuning, which have shown that the importance of tuning increases with the potential for turbines to exert thrust on the incoming flow and hence affect their own performance [15,18]. The results are also consistent with present understanding of array performance: as B L increases (and B A reduces) for a given N (or as N increases and B A reduces for a given B L ), an array-scale bypass flow is introduced and a reversal boost dynamic is established [8].…”
Section: Dynamic Tuningsupporting
confidence: 92%
“…As before, different turbine arrangements are considered and the maximum time-averaged available power is compared between the different turbine models. This part extends not only the work of Bonar et al [8] to include dynamic tuning, but also the work of Chen et al [15] to include partial-width turbine arrays. Although the computational demands of the numerical scheme used to calculate the optimal tuning curves limit the study to a single channel and small number of turbine arrangements, the present paper is, to our knowledge, the first to explore the combined effects of local blockage and dynamic tuning on tidal turbine performance.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations